Aptamer-based microcantilever array biosensor for detection of fumonisin B-11. Issue 45 (20th May 2015) - Chen, Xuejuan; Bai, Xiaojing; Li, Huiyan; Zhang, Bailin
<x xml:space="preserve">Abstract</x> An aptamer-based microcantilever array sensor was developed for the detection of FB1 with a LOD of 33 ng mL−1.